Pengaruh Kepemimpinan Transformasional, Struktur Organisasi terhadap Kapasitas Inovasi Yang di Mediasi Budaya Pembelajaran Survey Pada ASN Kantor Camat Aur Birugo Tigo Baleh - Khairiah, Nadiatul (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
This study aims to analyze the effect of transformational leadership, organizational structure on innovation capacity mediated by learning culture in the Aur Birugo Tigo Baleh sub-district, Bukittinggi City. This study uses a quantitative approach because the observed symptoms are converted into numbers that are analyzed using statistics. The author chose the sample using a saturated sampling technique because the population is relatively small. So that the sample used in this study amounted to 78 people. The purpose of this study was to determine the effect of each variable on Transformational Leadership (X1), Organizational Structure (X2) and Learning Culture (Z) on Innovation Capacity (Y). The results of the analysis show that the variables (X1) Transformational Leadership and (X2) Organizational Structure have a significant and positive effect on Innovation Capacity (Y) which also has an effect and Learning Culture (Z) with transformational leadership (X1) has an effect on innovation capacity (Y) as well. learning culture (Z) has a positive and significant effect on innovation capacity (Y). It can be concluded that Transformational Leadership and Organizational Structure have a positive and significant impact on the capacity of innovation through a learning culture.